2003
DOI: 10.1046/j.1365-2516.2003.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of inhibitors in haemophilia A: a systematic review

Abstract: This paper emphasizes the importance of distinguishing between the prevalence, incidence and cumulative incidence of inhibitors in haemophilia A. Incidence and cumulative incidence data will include patients with transient inhibitors or whose inhibitors have been eliminated by treatment. As these will not be included in prevalence data, prevalence studies will tend to give rise to lower figures than incidence studies. As a result, the most accurate estimates of the true risk of inhibitor development comes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
541
6
22

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(586 citation statements)
references
References 54 publications
17
541
6
22
Order By: Relevance
“…In a cohort of 316 subjects, Gouw et al found that there was no association between the type of product used and inhibitor development. 32 In addition, since the rate of nontransient inhibitor development in prospective trials of new recombinant products was similar to studies using plasmaderived products 33,34 ; and inhibitor formation is rare in previously treated patients who are switched to recombinant products 33,35,36 ; we believe the overall weight of the data suggests that there is no association between the type of fVIII product and inhibitor formation. Thus, we do not consider the risk of inhibitor formation when selecting a fVIII product to use for an individual patient.…”
Section: Treatment-related Risk Factorsmentioning
confidence: 62%
“…In a cohort of 316 subjects, Gouw et al found that there was no association between the type of product used and inhibitor development. 32 In addition, since the rate of nontransient inhibitor development in prospective trials of new recombinant products was similar to studies using plasmaderived products 33,34 ; and inhibitor formation is rare in previously treated patients who are switched to recombinant products 33,35,36 ; we believe the overall weight of the data suggests that there is no association between the type of fVIII product and inhibitor formation. Thus, we do not consider the risk of inhibitor formation when selecting a fVIII product to use for an individual patient.…”
Section: Treatment-related Risk Factorsmentioning
confidence: 62%
“…Two systematic reviews published in 2003 showed a significantly lower incidence of inhibitor development with the use of single pdFVIII product over a single rFVIII product; these reviews are summarized in Table 3. 15,16 However, after adjusting for study design, study period, testing frequency, and median follow-up, these data lost statistical significance in the second larger review. 16 The above data are largely retrospective, and a multivariate analysis of the studies in the second review showed an overestimation of inhibitor development in the retrospective studies.…”
Section: Prophylaxismentioning
confidence: 97%
“…The development of antibodies that inhibit or neutralize factor VIII (FVIII) replacement therapy occurs in as many as 20% to 30% of patients with severe hemophilia A and represents one of the most serious complications of hemophilia [1][2][3]. Inhibitors typically develop in early childhood, within the first 10-20 exposures to FVIII concentrates [2].…”
Section: Introductionmentioning
confidence: 99%